An asymptotic model for a thin, soft and imperfectly bonded elastic joint - Christian Licht (2018)
Copyright © 2015 John Wiley & Sons, Ltd. An asymptotic model for a thin, soft, linearly elastic joint imperfectly bonded to two linearly elastic bodies is derived by studying the variational convergence of the total mechanical energy when the thickness and the stiffness of the joint go to zero. The joint is replaced by a mechanical constraint between the adherents which correspond to the connection in series of the classical limit constraint induced by the soft joint and constraints between the joint and the adherents.